Nilai-Nilai Karakter Religius dalam Novel “Negeri 5 Menara” Karya Ahmad Fuadi - Saraswati Saraswati (SOCIETIES: Journal of Social Sciences and Humanities, 2022)
Abstract. This study aims to (1) describe the values of spiritual religious characters in the novel